APPLICATION OF DIAFILTRATION TO INCREASE FRUCTOOLIGOSACCHARIDES'PURITY BY MEMBRANE DS-5-DL - Hồng Ánh, Lê Thị; Anh Đào, Đồng Thị; Như Nguyện, Nguyễn Đình Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARYThis article presented results of application of diafiltration in fructooligosaccharides by membrane DS-5-DL. Under conditions of temperature of 45ºC, feed concentration of 5% (w/v), flow rate of 6 l/min and pressure of 25 bar, applying diafiltration of CVD and VVD, the relationship between FOS’s concentration and diafiltration step as well as the correlation between FOS’s yield and purity were determined. The highest purity was 86.84% in VVD mode with ratio of flow rate of dilution water/permeate of 0.90/1.